Preparation and Evaluation of Potent Pentafluorosulfanyl‐Substituted Anti‐Tuberculosis Compounds. (27th June 2017) - Moraski, Garrett C.; Bristol, Ryan; Seeger, Natalie; Boshoff, Helena I.; Tsang, Patricia Siu‐Yee; Miller, Marvin J.
Abstract: The global fight to stop tuberculosis (TB) remains a great challenge, particularly with the increase in drug‐resistant strains and a lack of funding to support the development of new treatments. To bolster a precarious drug pipeline, we prepared a focused panel of eight pentafluorosulfanyl (SF5 ) compounds which were screened for their activity against Mycobacterium tuberculosis (Mtb) H37Rv in three different assay conditions and media. All eight compounds had sub‐micromolar potency, and four displayed MICs <100 nm . Seven compounds were evaluated against non‐replicating and mono‐drug‐resistant Mtb, and for their ability to inhibit Mtb within the macrophage. The greatest potency was observed against intracellular Mtb (MIC <10 nm for three compounds), which is often the most challenging to target. In general, the SF5 ‐bearing compounds were very similar to their CF3 counterparts, with the major differences observed being their in vitro ADME properties. Two SF5 ‐bearing compounds were found to have greater protein binding than their corresponding CF3 counterparts, but were also less metabolized in human microsomes, resulting in longer half‐lives. Abstract : A focused set of pentafluorosulfanyl (SF5 ) compounds were prepared and evaluated against Mycobacterium tuberculosis (Mtb) H37Rv in multiple assays. Overall, the compounds demonstrated great potency against replicating Mtb, particularly within the macrophage. However, in other evaluations (non‐replicating Mtb, drug‐resistant Mtb, minimum bactericidal concentration, and toxicity) these compounds began to show differences between each other.